AN ALGORITHM TO REDUCE FACES IN 3D MODELS - Toàn, Đỗ Năng; Huân, Nguyễn Văn (Vietnam Journal of Science and Technology, 2012)
SUMMARYThis paper deals with a technique to reduce faces in 3D models based on Angles algorithm in 2D, by calculating angle between two normal faces, that have the same edge. The given technique seems be effective for approximately flat surfaces.